Dielectric and ferroelectric properties of lead zirconate titanate-barium titanate ceramics prepared by a modified mixed-oxide method - Wanwilai Chaisan (2018)
Ceramic solid solutions within the system (1 - x)Pb(Zr0.52Ti0.48)O3-xBaTiO3, where x ranged from 0.0 to 1.0, were prepared by a modified mixed-oxide method. The crystal structure, microstructure, dielectric and ferroelectric properties of the ceramics were investigated as a function of composition via X-ray diffraction (XRD), scanning electron microscopy (SEM), dielectric spectroscopy and hysteresis measurement. The (1 - x)PZT-xBT solid solutions showed that with increasing solute concentration (BT or PZT), the phase transformation became diffuse. This was primarily evidenced by an increased broadness in the dielectric peak, with a maximum peak width occurring at x = 0.5. The P-E hysteresis loop measurements showed that while BT showed a well-formed hysteresis loop, PZT and 0.1PZT-0.9BT ceramics exhibited pinched-shape hysteresis loops due to abnormal domain switching mechanism. In addition, other compositions exhibited very slim-loop hysteresis occurred in materials with mixed phase or with diffuse phase transition. This observation was believed to be caused by nano-scaled chemical heterogeneity in these compositions. © 2007 Elsevier B.V. All rights reserved.